Pelatihan olah seni vokal berbasis elekton pada murid autis di SLB Negeri 1 Makassar - Abdul Hadis; Mustafa Mustafa; Usman Usman (DEDIKASI, 2020)
This Community Partnership Program (PKM) in SLBN 1 Makassar City. The formulation problem is: disability students who are autistic as students who experience disabilities both in terms of mental aspects and in terms of communication disorders. But, have a number of potential that should be proud of his parents, siblings, environment, and at school community, nation and state. Potential superior in question is superior talent in vocal arts, music, classy call to pray, and other potentials. This fact was demonstrated by one of the students of the PLB FIP UNM Department, demonstrating an extraordinary talent in playing electronic keyboards while singing (musical talent), even though they were very blind. In the commemoration of international disability day in the auditorium of Amanagappa, there were autistic children with talent in vocal arts. The external target was training in singing national anthems. The method used was lecture and training. The results achieved were the four autistic children who were trained in electronic-based vocals were able to sing two national anthems, namely independence day and cheers.